RSU placement optimization in vehicular participatory sensing networks - Teerawat Kumrai (2018)
This paper proposes a multi-objective optimization evolutionary algorithm for placement of roadside units (RSUs) in participatory sensing using vehicular networks. The proposed algorithm heuristically optimizes RSUs' communication coverage area in a city with the minimal number of RSUs. The extensive simulation results show the efficacy of the proposed algorithm comparing to a traditional placement algorithm. © 2014 IEEE.